Single-cell RNA profiling of colorectal granular-type laterally spreading tumor uncovers progression trajectory toward carcinoma and transcriptional signatures favoring lateral morphogenesis - Gong, Yueqing; Zhang, Yuxin; Liu, Xun; Cui, Rongli; Lu, Jingjing; Li, Jun; Gu, Fang; Zhang, Jing; Ding, Shigang; Fu, Weiwei (Frontiers in Oncology, 2025)
BackgroundColorectal laterally spreading tumors (LSTs) are defined as non-protruding neoplasms exceeding 10 mm in diameter that grow primarily along the intestinal wall. The morphogenetic mechanisms and evolutionary trajectories of granular-type LSTs (LST-Gs) towards colorectal carcinoma remain unclear.MethodsIn this study, we investigate the transcriptional features of LST-Gs using single-cell RNA sequencing technology by comparing them with protruded-type adenomas (PAs) and normal mucosal tissues.ResultsAdenomatous LST-Gs harbor an epithelial cell population with metaplastic differentiation, which are almost absent in PAs. Cells with a high degree of differentiation in LST-G demonstrate enhanced immunogenicity and robust adhesion/junction interactions. Furthermore, LST-Gs show upregulated expression of molecular chaperones and metallothioneins compared to PAs, reflecting a more hostile microenvironment similar to that observed in carcinoma stages. These characteristics suggest that LST-G exhibits greater heterogeneity compared to the earliest colorectal adenomas, mirroring the progression from precancerous states to cancer. Notably, the Arp2/3 complex is significantly upregulated in highly differentiated LST-G cell populations, potentially facilitating cell migration along the basement membrane, which highlights the similarities in cell motility between adenomatous LST-G and normal mucosal epithelium as well as serrated polyps (SERs).ConclusionThe differentiation state of cells within LST-G exhibits a close correlation with their diverse characteristics. Metaplastic differentiation, as a prominent feature at the transcriptional level, demonstrates significant associations with the genomic features, morphogenesis, and tumor progression of LST-G.